Monitoring The Water Leakage System (MWLS) using an Ultrasonic Sensor - Gati , Muhammad 'Atif; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2022)
Water waste in the current scenario is simply due to overflowing tanks, which is unsustainable. Conventional water tanks cannot monitor or control the water level in the tank, resulting in significant water waste. Other technologies had some drawbacks in one way or another. The main goal of this project has been to eliminate these flaws while also providing an efficient and cost-effective solution. Our project uses IoT and Blynk applications to monitor and control water levels. Arduino is an open-source IoT platform that we are using. An HC-SR04 ultrasonic sensor is placed on the tank’s surface to sense the water level and the distance between the sensor and the water level is measured and sent to the Blynk application via Arduino. We can manually monitor the tank by using an on/off button provided in the Blynk app. The Blynk app has a user interface that displays the tank layout and a manual operation button.